‘n Voorlopige Afrikaanse weergawe van die Phonological Awareness Literacy Screening-Kindergarten (PALS-K) (Afrikaans) - Louw, Brenda (University of Pretoria, 2013)
Dissertation (M (Communication Pathology))--University of Pretoria, 2006.